2013
DOI: 10.1002/acr.21978
|View full text |Cite
|
Sign up to set email alerts
|

Association of High Body Mass Index With Decreased Treatment Response to Combination Therapy in Recent‐Onset Rheumatoid Arthritis Patients

Abstract: Objective. To assess the association between high body mass index (BMI) and treatment response in recent-onset rheumatoid arthritis. Methods. In the Behandelstrategieën voor Reumatoide Artritis (Treatment Strategies for Rheumatoid Arthritis) study, 508 patients were randomized to initial monotherapy or combination therapy with prednisone or infliximab (IFX). The response to Disease Activity Score (DAS) <2.4 -steered treatment (first dose and after 1 year) was compared between patients with a BMI <25 kg/m 2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
97
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 16 publications
6
97
0
4
Order By: Relevance
“…32 Furthermore, 1596 obese patients with early RA were monitored for a mean 9.5±3.7 years, when compared with patients with normal weight, it turn out that obesity early and during follow up was strongly related to higher disease activity (mean DAS28 3.0±1.2 vs. 2.7±1.3, P = 0.002), less sustained remission rate (20.5% vs 26.6%; p=0.048) and increase in the mean pain level (32.9±23.9 vs 25.8±23.8; p=0.005). 33,34 The rise in DAS28 observed in these studies appeared to be subjectively influenced ( number of sore joints as well as patients overall assessment [34][35][36] ) and not linked to C reactive protein level or ESR. 36,37 In two studies, Health Questionnaire Assessment (HAQ) was recruited to assess functional disability in RA patients.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…32 Furthermore, 1596 obese patients with early RA were monitored for a mean 9.5±3.7 years, when compared with patients with normal weight, it turn out that obesity early and during follow up was strongly related to higher disease activity (mean DAS28 3.0±1.2 vs. 2.7±1.3, P = 0.002), less sustained remission rate (20.5% vs 26.6%; p=0.048) and increase in the mean pain level (32.9±23.9 vs 25.8±23.8; p=0.005). 33,34 The rise in DAS28 observed in these studies appeared to be subjectively influenced ( number of sore joints as well as patients overall assessment [34][35][36] ) and not linked to C reactive protein level or ESR. 36,37 In two studies, Health Questionnaire Assessment (HAQ) was recruited to assess functional disability in RA patients.…”
Section: Resultsmentioning
confidence: 95%
“…33,34 The rise in DAS28 observed in these studies appeared to be subjectively influenced ( number of sore joints as well as patients overall assessment [34][35][36] ) and not linked to C reactive protein level or ESR. 36,37 In two studies, Health Questionnaire Assessment (HAQ) was recruited to assess functional disability in RA patients. The score was significantly higher in obese patients than in normal weight patients (0.6±0.7 vs. 0.5±0.6; P <0.001, and +0.16 (95% CI 0.03 to 0.30) respectively).…”
Section: Resultsmentioning
confidence: 95%
“…Recent reports showed a negative association between BMI and response to anti-TNF␣ therapies, notably infliximab (IFX), in RA [13][14][15], psoriatic arthritis [16,17] and ankylosing spondylitis (AS) [18,19], which suggests that fat mass may affect the response to biologic agents. BMI might be a predictive factor of IFX response in RA, but no study has evaluated the impact of BMI on rituximab (RTX) response in RA.…”
Section: Introductionmentioning
confidence: 98%
“…For example, several high-quality studies have demonstrated that RA patients with a higher body mass index (BMI, a surrogate for adiposity), have lower all-cause and CVD mortality 13 , and tend to be protected from erosive damage 14 . This protection is found to exist despite the observation that RA patients with higher BMI tend to have higher measures of disease activity than those with lower BMI, and a diminished treatment response to some biologic disease-modifying antirheumatic drugs 15 . Clearly, the relationships that link the inflammatory products of adipose tissue with RA-associated outcomes are complex, dynamic, possibly conditioned on other patient-specific features, and not easily explained using simple correlations and bivariate modeling techniques.…”
mentioning
confidence: 48%